Finding a predictive equation for the speed of the legs' forward movements index in terms of some sensory-motor abilities among young fencers (Damu Journal of Sport Sciences, 2024)
The aim of this research is to study the factors affecting the speed of the legs' forward movements in the sport of fencing, in terms of some sensory-motor abilities such as perception of distance and perception of force. Understanding these variables is vital to improving the performance of fencers in various competitions. A weighted multiple linear regression model was used to analyze the relationship between these variables and the speed of the feet' forward movements, which directly affects offensive and defensive performance. Data were collected from a group of fencers, where the speed of the feet' forward movements was measured, in addition to their perception of the three factors: distance, force, and time. The results showed significant differences at a significance level of (0.05) for the variables of distance perception and speed of foot movements, indicating the importance of distance perception as a major factor in improving the motor performance of fencers. On the other hand, no significant differences were found for the variables of force perception and time, reflecting their lack of significant impact on the speed of foot movements in fencing. Accordingly, a predictive model was developed that can be used to estimate fencers' performance based on the results of distance perception and movement speed. It recommended the importance of training fencers to improve distance perception, as it is considered an essential factor in improving performance in fencing, with a focus on developing training programs targeting this sensory aspect to enhance rapid response and accuracy in movements.